Factors affecting the level of customer deposit: the case of commercial banks in Vietnam - Le, Vinh; Pham, Quang; Bui, Thanh; Nguyen, Phuong (Journal of International Economics and Management, 2023)
This study aims to evaluate the factors affecting the level of customer deposits in Vietnamese commercial banks. The research sample includes 25 banks from 2009 to 2021. The secondary data were collected from the audited financial statements of banks and the statistical information of the Hanoi and Ho Chi Minh Stock Exchanges. The regression results show that bank profitability, loan quality, listing status, and state-controlled ownership have a positive effect on the level of customer deposits, while bank liquidity, average interest rate, and global financial crisis negatively affect the level of customer deposits. According to these results, commercial banks should focus on developing benefits for depositors and strategies to build customer trust and confidence to increase the level of customer deposits. The findings also imply the positive role of deposit insurance and the State Bank, together with the government, in mobilizing deposits from customers. Our study provides reliable empirical evidence of the impact of state controlled ownership, stock listing, and global financial crisis on the level of customer deposits. Bank managers and other stakeholders attract deposits from customers, and the findings add to the evidence for developing related theories.